A luminescence study of Cu2ZnSnSe4/Mo/glass films and solar cells with near stoichiometric copper content. (28th November 2018) - Yakushev, M V; Sulimov, M A; Márquez-Prieto, J; Forbes, I; Edwards, P R; Zhivulko, V D; Borodavchenko, O M; Mudryi, A V; Krustok, J; Martin, R W
Abstract: Cu2 ZnSnSe4 (CZTSe) is one of the leading candidates for the absorber layer in sustainable solar cells. Thin films of CZTSe with a near stoichiometric [Cu]/[Zn + Sn] were used to produce solar cells with conversion efficiency η = 6.4% by a standard solar cell processing including KCN etching and the deposition of CdS and ZnO. Both CZTSe films and solar cells were examined using photoluminescence (PL) to analyse the nature of radiative recombination and photoluminescence excitation (PLE) at 4.2 K to determine the bandgap ( E g ). Low temperature PL spectra of the films reveal an intense band P1 at 0.81 eV and a low intensity band P2 at 0.93 eV. Their temperature and excitation intensity dependencies suggest that they both involve recombinations of free electrons with holes localised at acceptors with the energy level influenced by potential fluctuations in the valence band. We associate P1 and P2 with different fractions of CZTSe: with a lower and higher degree of order of Cu and Zn on the cation sub-lattice, respectively. Device processing reduced the intensity of P1 by 2.5 whereas the intensity of P2 increased by a 1.5. We assign this to a low temperature annealing due to CdS and ZnO deposition which increased the fraction of CZTSe with high degree of Cu/Zn order and decreased the fraction with low degree of Cu/Zn order. Device processing increased E g, blue shifted P1, decreased its width, j- shift and the mean depth of potential fluctuations. These can also be related to the annealing and/or KCN etching and the chemical effect of Cd, due to CdS replacing copper at the CdS-CZTSe interface layer. Processing induced a new broad band P3 at 1.3 eV (quenching with E a = 200 meV) which we attributed to defects in the CdS layer.